Trophic interaction network and the evolutionary history of Diabroticina beetles (Chrysomelidae: Galerucinae) - Eben, Astrid; Espinosa de los Monteros, Alejandro (Journal of applied entomology, 2015)
Understanding the striking diversity of species in the subtribe Diabroticina (Chrysomelidae: Galerucinae: Luperini) is complicated by a lack of ecological and behavioural observations. Adults are mainly pollen feeders and their feeding habits range from highly polyphagous to oligophagous on a single host family. Host breadth for root-feeding larvae and for adult feeding and oviposition remains largely unknown for the majority of non-pest species. We used known host plant associations for 43 species of Diabroticina beetles in six genera to summarize trophic interactions between beetles and host plant families. The metrics of ecological network analyses (connectance, modularity, number of interactions and feeding specialization) revealed a heterogeneous pattern of interactions. Most species are connected with few host plants, whereas few species interact with many hosts. A more robust analysis is likely to emerge when a greater representation of neotropical Diabroticina and their host relationships is obtained.
Gesehen am 02.07.2020